The Production Space of Thai Learners’ Mandarin Chinese and Thai Tones - Pornrattananukul, Apisara (Journal of Sinology (วารสารจีนวิทยา), 2013)
Thai language undoubtedly has effects on Thai learners’ Mandarin Chinese tone learning. That means Thai learners have to confront the difficulties and problems in learning Mandarin Chinese. In order to investigate the problems, this study will analyze the production space of Thai learners’ Mandarin Chinese and Thai tones, based on the similarity of the two languages’ tones, as the experiment can demonstrate the development and problems of the production on Thai learners’ Mandarin Chinese tones.